2012
DOI: 10.1177/1758834012444711
|View full text |Cite
|
Sign up to set email alerts
|

Triple-negative breast cancer: are we making headway at least?

Abstract: Abstract:The so-called triple-negative breast cancer, as defined by tumors that lack estrogen receptor, progesterone receptor and human epidermal growth factor receptor 2 (HER2) overexpression, has generated growing interest in recent years despite representing less than 20% of all breast cancers. These tumors constitute an important clinical challenge, as they do not respond to endocrine treatment and other targeted therapies. As a group they harbor an aggressive clinical phenotype with early development of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 97 publications
0
63
0
Order By: Relevance
“…TNBC is characterized by a lack of the expression of the ER, progesterone receptor and HER-2 [43]. It accounts for about 17% of all breast cancers, representing an aggressive clinical behavior and is generally associated with poor prognosis; thus chemotherapy remains the only systemic treatment option available for these patients [43]. Accordingly, there is a need to develop new treatments for this aggressive subtype, which currently lack targeted therapy.…”
Section: Resultsmentioning
confidence: 99%
“…TNBC is characterized by a lack of the expression of the ER, progesterone receptor and HER-2 [43]. It accounts for about 17% of all breast cancers, representing an aggressive clinical behavior and is generally associated with poor prognosis; thus chemotherapy remains the only systemic treatment option available for these patients [43]. Accordingly, there is a need to develop new treatments for this aggressive subtype, which currently lack targeted therapy.…”
Section: Resultsmentioning
confidence: 99%
“…TNBC is associated with shortened disease-free interval post-surgery and post-adjuvant treatment and, ultimately, a shortened overall survival. [12][13][14][15] Furthermore, TNBCs are themselves a heterogeneous group within which the claudinlow subtype is associated with worst prognosis. 16 Compared to the overall prevalence of breast cancer, a limited number of reports have indicated exosomes and/or microvesicles to be of relevance in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular substudy of CALGB 9342 demonstrated that patients with TNBC had a shorter median survival with metastatic disease than non-TNBC patients (8.6 versus 12.8 months; p = 0.009) [19]. It has been suggested that they seem to respond to chemotherapy better than other types of breast cancer, but prognosis remains very poor, if treated by conventional chemotherapy [20,21]. There were some trials to deploy the clinical responses through different chemotherapeutic regimens in the settings of the neoadjuvant, adjuvant, metastatic in pursuing of obtaining reliable responses.…”
Section: Discussionmentioning
confidence: 96%